(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In this thesis study, 4,4'-Bis(3-phenyl-3-methylcyclobutyl)-2,2'-bithiazole (C28H28N2S2) the single crystal structure consisting of some compound groups such as thiazole, and phenyl was synthesized and characterized by IR, 1H NMR, and 13C NMR techniques. The molecular structure of the single crystal structure consisting of compounds that have a common usage area was analyzed by X-ray diffraction technique. The compound C28H28N2S2 was found to be in the monoclinic crystal system and the P21/c space group. The unit cell parameters of the molecular structure were obtained at a= 5.8461(6)Å, b= 35.806(4) Å, c= 11.6538(11) Å, α=γ= 90° and β= 93.774(8)°, z =4, and (volume) V= 2434.2(4) Å3 from the X-ray diffraction results. It is seen that the molecular structure C28H28N2S2 in the asymmetric unit is in a symmetrical structure. When the bond parameters of the molecular structure were compared with similar studies, the bond parameters were found to be quite compatible. The molecular structure C28H28N2S2 classically does not contain an intermolecular or intramolecular hydrogen bond.. However, the C–H…π interactions have been observed between the phenyl carbon atoms and the phenyl ring centers, which allow the molecular structure to be stacked in space.